PERTUMBUHAN JUVENIL LABI-LABI (Amyda cartilaginea) BERDASARKAN UJI COBA PREFERENSI PAKAN DI PENANGKARAN PT. ARARA ABADI, KABUPATEN SIAK. - Ningsih, Yelfi Dwi; Yoza, Defri; Sulaeman, Rudianda (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
Trionychia (Amyda cartilaginea) was a species that categorized in Appendix II of CITES and vulnerable or risky in IUCN Red List Data Book. Captivity was one way to support the conservation efforts of these animals and it germplasm.Captivity done to maintain endangered animals like Trionychia.This research aims to measure level of consumption and preference feed of juveniles Trionychia on some type of feed given on captivityof PT. Arara Abadi, Siak. Method of collecting data used was observation,whichconducted through direct observation of objects to be researched.Feed which tested in feed preference were cork fish saplings, shrimp saplings, cassava and kale that was given to 15 juvenilesfeed trial and measured the consumption level of feed and growth. The resultofthis research indicatelevel ofthe highestshrimpsaplings consumptionduring the research were 56,424g. First preference feedofshrimp saplings were 0,37g, cassava 0,34gandcork fish saplings 0,27g.Growth of juvenil trial for fiveweeks was 0,1 g/tail/day. Keywords: Amydacartilaginea, captivity, feed